Living Kidney Donors' Financial Expenses and Mental Health. Issue 6 (June 2021) - Barnieh, Lianne; Arnold, Jennifer B.; Boudville, Neil; Cuerden, Meaghan S.; Dew, Mary Amanda; Dipchand, Christine; Feldman, Liane S; Gill, John S.; Karpinski, Martin; Klarenbach, Scott; Knoll, Greg; Lok, Charmaine; et al.
Abstract : Background: Living kidney donors incur donation-related expenses, but how these expenses impact postdonation mental health is unknown. Methods: In this prospective cohort study, the association between mental health and donor-incurred expenses (both out-of-pocket costs and lost wages) was examined in 821 people who donated a kidney at one of the 12 transplant centers in Canada between 2009 and 2014. Mental health was measured by the RAND Short Form-36 Health Survey along with Beck Anxiety Inventory and Beck Depression Inventory. Results: A total of 209 donors (25%) reported expenses of >5500 Canadian dollars. Compared with donors who incurred lower expenses, those who incurred higher expenses demonstrated significantly worse mental health–related quality of life 3 months after donation, with a trend towards worse anxiety and depression, after controlling for predonation mental health–related quality of life and other risk factors for psychological distress. Between-group differences for donors with lower and higher expenses on these measures were no longer significant 12 months after donation. Conclusions: Living kidney donor transplant programs should ensure that adequate psychosocial support is available to all donors who need it, based on known and unknown risk factors. Efforts to minimize donor-incurred expenses and to better support the mental well-being of donors need to continue. Further research is needed to investigate the effect of donor reimbursement programs, which mitigate donor expenses, on postdonation mental health. Abstract : Supplemental Digital Content is available in the text.